STUDI PEMANFAATAN PASIR LAUT SEBAGAI AGREGAT HALUS PADA CAMPURAN BETON ASPAL - Ramlan, Ratnasari; Pradhani, Novita (MEKTEK, 2008)
The purpose of this Research is to know sand quality and exploiting go out to sea as smooth aggregate for a concrete mixture asphalt. Where to determine made by optimum asphalt content 5 object test with asphalt rate variation, that are 5%, 5,5%, 6%, 6,5% and 7%. After obtaining optimum asphalt content value that is 6,4% hereinafter will be made by object test by using optimum asphalt rate. Sand condition to be used by is the condition of sea sand influenced by up and down of water sea, condition of sea sand which do not influenced by up and down of water sea, Sand condition influenced by up and down of water sea which have washed out. For three conditions of the sand tested by Marshall (measuring tool) with time variation of submersion that is 30 minutes, 1 hour, 3 hours, 5 hours and 24 hours. The obtained data is the condition of sea sand that influenced by up and down of sea, do not fulfill the specification of discharge, where sand discharge go out to sea above 4,5 mm.